Innovation in Digital Marketing Erigo Indonesia during Pandemic Covid-19 - Mega Riani; Umanto Umanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to describe the concept of innovation in digital marketing MSMEs in Indonesia during pandemic covid-19 and still be number one as a local brand in Indonesia. The research used literature study. From the results of the literature study above Erigo is able to comprehensively carry out marketing concepts by taking advantage of pandemic conditions. The existence of a pandemic does not reduce Erigo's innovation and steps as a child of the nation to provide the best for Indonesia so that MSMEs and Indonesia will still have a place in the eyes of the world.